The effects of fermentation of Qu on the digestibility and structure of waxy maize starch - Wu, Wenhao; Zhang, Xudong; Qu, Jianzhou; Xu, Renyuan; Liu, Na; Zhu, Chuanhao; Li, Huanhuan; Liu, Xingxun; Zhong, Yuyue; Guo, Dongwei (Frontiers in Plant Science, 2022)
The fermentation of Qu (FQ) could efficiently produce enzymatically modified starch at a low cost. However, it is poorly understood that how FQ influences the waxy maize starch (WMS) structure and the digestion behavior. In this study, WMS was fermented by Qu at different time and starches were isolated at each time point, and its physico-chemical properties and structural parameters were determined. Results showed that the resistant starch (RS), amylose content (AC), the average particle size [D(4,3)] the ratio of peaks at 1,022/995 cm–1, and the onset temperature of gelatinization (To) were increased significantly after 36 h. Conversely, the crystallinity, the values of peak viscosity (PV), breakdown (BD), gelatinization enthalpy (ΔH), and the phase transition temperature range (ΔT) were declined significantly after 36 h. It is noteworthy that smaller starch granules were appeared at 36 h, with wrinkles on the surface, and the particle size distribution was also changed from one sharp peak to bimodal. We suggested that the formation of smaller rearranged starch granules was the main reason for the pronounced increase of RS during the FQ process.